Induction of luteolin on postharvest color change and phenylpropanoid metabolism pathway in winter jujube fruit (Ziziphus jujuba Mill. cv. Dongzao) - Tang, Yisong (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.